Spike nanoparticles: From design to biomedical applications - Xiaohui Wang; Xin Fang; Xinmei Liu; Yuchao Lyu; Lishuang Ma; Jianye Fu (Next Materials, 2024)
Spike nanoparticles or virus-like nanoparticles are wonder materials by the very first impression, similar to the morphology of a virus with nanospikes distributed uniformly on the surface of nanoparticles. The past decades have witnessed great significant developments in the synthetic strategies, unique properties, and promising biomedical applications of spike nanoparticles. The unique surface topography of spike nanoparticles enables them with extraordinary advantages in various biomedical applications, such as drug delivery due to the strong nano-bio interactions. This review will focus on the distinguishing features of the spike nanoparticles, where the development of the novel drug delivery vectors capable of releasing the therapeutic cargo as designed to the tumor sites would be reviewed here, together with the widely accepted formation mechanisms and fabrication strategies. The huge progress in the design strategies and development of spike-structured nanomaterials for drug delivery based applications will be collated here. The current challenges are proposed regarding on the synthesis techniques and future perspectives of spike nanoparticles. This timely review should be desirable for broad scientists and facilitate the further development of spike nanoparticles.